PHRASAL VERBS AND METHODS OF ITS CLASSIFICATION IN LINGUISTICS - Abdumannofov Shamsiddin Mehriddin o'g'li (Journal of new century innovations, 2022)
To this point, we have recognized several fundamental components, including Adjectival Phrases, Noun Phrases, and Prepositional Phrases. We are aware that verbs are capable of performing the duties of predicates and that in order to make a sentence, verbs must unite with a subject and an object.